Comparison between the specificity and sensitivity of the RIPASA and Alvarado Scoring systems in the diagnosis of acute appendicitis among patients with complaints of right iliac fossa - Seyed Ashkan Tabibzadeh Dezfuli; Reza Yazdani; Mohammadjavad Khorasani; Seyed Alireza Hosseinikhah (AIMS Press, 2020)
Introduction: Acute appendicitis is one of the common prevalent surgical emergencies. Various techniques, such as Alvarado Score are used for diagnosis it. This study was conducted to compare the Alvarado and RIPASA scoring systems in patients referred to Hospital with complaints of right iliac fossa pain. Methodology: This descriptive-analytic cross-sectional study was conducted in patients over 15 years with abdominal pain referred to emergency room of the Hospital. The data collection form was completed for each patient based on history and examinations and then examined by a surgeon. The pathological specimens were examined and the pathological outcomes of each patient were recorded in the relevant information collection form and finally analyzed. Results: The results for the Alvarado system showed that 42.1%, 29.2% and 28.80% of the patients had a low probability, moderate probability and high probability of appendicitis, respectively. The findings for RIPASA system showed that 19.3% of patients definitely had appendicitis. The sensitivity and specificity of the Alvarado scoring system were 53.95% and 70.18%, respectively. Positive and negative predictive values of Alvarado were 70.69% and 53.33%, respectively. In contrast, the sensitivity, specificity, and positive and negative predictive values of the RIPASA scoring system were 93.42%, 45.61%, 69.61%, and 83.87%, respectively. Conclusion: On the basis of the results, the RIPASA scoring system is a better system. Since the best cut-off point is 6 for Alvarado and 7.75 for RIPASA, it is better to use the values as a benchmark for the systems.